Spiritual Activities, Self-Reflection, and Social Support: Increasing Female Inmates' Self-Compassion - Widya Pusvita Adina; Mustamira Sofa Salsabila; Syafrimen Syafril (Yayasan Keluarga Guru Mandiri, 2025)
This study was motivated by issues surrounding the understanding of self-compassion as an essential psychological resource for female inmates in dealing with pressure, stigma, and life limitations in correctional facilities. Self-compassion, which includes self-kindness, common humanity, and mindfulness, plays a crucial role in reducing depression and anxiety while enhancing mental well-being. However, its application among female inmates remains limited due to traumatic experiences and high social pressure. Therefore, this study aims to analyze how self-compassion is understood and developed among female inmates at the Class II A Correctional Facility in Bandar Lampung. This qualitative research employed a Single Holistic Case Design involving three female inmates as primary informants and five significant others (four inmates and one staff member) selected through purposive sampling. Data were collected through in-depth interviews, observations, and document analysis, and were analyzed thematically using NVivo 12 Plus software. The results reveal that self-compassion develops through spiritual activities, self-reflection, and social support despite severe psychological distress. The findings highlight the role of spirituality and social bonds in fostering psychological resilience. This study contributes to the scientific understanding of self-compassion in correctional contexts and provides implications for developing context-based rehabilitation programs for female inmates.